Infrastructure, Integrity, and Achievements of Female Local Leaders: a Perspective on Decentralization Politics - Robert Endi Jaweng (Jurnal Perempuan, 2014)
Dezentralization and local autonomy marks the shift of power from centre to the locals. In the political transition landscape, the actual cause in Indonesia is the power relations that should investigate further dimension of gender, social, politics, and economy. Within this network and framework, women’s leadership are hoped to nurture equality and prosperity for those being othered by development and growth. This paper concludes that executive leadership that promotes gender equality shall, foremost, promote concept of women’s leadership which are not only due to inheritance but basic political infrastructure.